6-3+4x+1=y

Simple and best practice solution for 6-3+4x+1=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3+4x+1=y equation:


Simplifying
6 + -3 + 4x + 1 = y

Reorder the terms:
6 + -3 + 1 + 4x = y

Combine like terms: 6 + -3 = 3
3 + 1 + 4x = y

Combine like terms: 3 + 1 = 4
4 + 4x = y

Solving
4 + 4x = y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 4x = -4 + y

Combine like terms: 4 + -4 = 0
0 + 4x = -4 + y
4x = -4 + y

Divide each side by '4'.
x = -1 + 0.25y

Simplifying
x = -1 + 0.25y

See similar equations:

| 9x+4=5[x-(5-x)] | | 13=7x+1-5x | | 2(y-5)=5y-4 | | 13=7x+1-5 | | tan(68)=4/x | | .93=x/50 | | 8(x-1.6)=4.8 | | 9n=243 | | 5x+8=5-2(3x+7) | | 3x+5y+3xy=12 | | (5x+3)2+(11x-15)=180 | | (11x-44)(x-7)=0 | | 735/783=50/x | | 1-2(-2)=y | | E(x)=130x+104 | | n-19=36 | | (x^2)-8x+10=0 | | 3(2d+7)=16 | | n+26=97 | | 1/3^2-11x-4=0 | | C=1725/9(F-950) | | X(3x-7)(2x+5)=0 | | 0.12*m=6.0 | | 5^t/2=9 | | (5x+3)2=(11x-15) | | 3X^2-11x+4= | | 0.2x+0.5=-1.1 | | X(x+1)=6480 | | y-6=6(x-10) | | X^2+x=6480 | | 4/(x-2)=10 | | x+(x*0.25)=125 |

Equations solver categories